Policing digital crime - Bryant, Robin; Bryant, Sarah (Ashgate Publishing Company, 2014)
This timely volume offers a theoretical perspective on the policing of digital crime in the western world. Using numerous case-study examples to illustrate the theoretical material introduced this volume examine the organisational context for policing digital crime as well as crime prevention and detection.